The clinical boundary between deviant behavior and criminal conduct: From maladaptive positions to pathological dysfunctionality using the "Graded Antisociality Model" (GA-M), the "Antisocial Severity Scale" (AS-S) and "Perrotta-Marciano questionnaire on - Giulio Perrotta; Antonio Marciano (Annals of Psychiatry and Treatment - Peertechz Publications, 2022)
The concepts of deviance and criminality are often confused or grouped, following a sociological logic. In the clinic, there is a need to distinguish them, speaking of "deviant behaviors" as active human acts that result in a violation of a social norm determined by the community and that do not provide a sanction of a legal nature (e.g., personal use of drugs)", while from "criminal behaviors" as active human acts that result in a violation of an exclusively legal norm and that provides a sanction of a civil-administrative nature (compensation for damages, restitution, demolition, suspension, disbarment, and administrative detention) or criminal (fine, fine, imprisonment and arrest)". Even more succinctly, we can consider "deviant and criminal behavior" (DCB) as all those active human acts that constitute a violation of a social and/or legal rule, and their transgression provides for the application of a punitive sanction. Based on this assumption, we propose a) the Graded Antisocial Model (GA-M), which considers antisociality as a graded phenomenon that is reinforced over time through active behaviors that are not limited by the social context of reference, becoming then a structured personality disorder only when the individual's self-centeredness becomes rigid and dysfunctional; b) the Antisocial Severity Scale (AS-S), which draws the pathological and dysfunctional evolution of antisociality, in five levels (yellow for emotional dysfunctionality, orange for self-centeredness, red for violation of social rules and violence to property, animals, and people, purple for severe violation of legal rules and black for structured psychopathology); c) the Perrotta-Marciano Questionnaire on the state of awareness of one's deviant and criminal behaviors (ADCB-Q), in 30 items on L1-6 scale, which defines both deviant and criminal tendency and the grade of awareness of one's pathological state.